"Not always a straight path": patients' perspectives following anterior cruciate ligament rupture and reconstruction. Issue 19 (11th September 2018) - Scott, Sarah M.; Perry, Meredith A.; Sole, Gisela
Abstract: Purpose: To explore patients' perspectives following anterior cruciate ligament rupture and subsequent reconstructive surgery. Methods: A qualitative study design was employed, using validated questionnaires, interviews and general inductive methodology. Semi-structured interviews were conducted with five men and four women who had undergone an anterior cruciate ligament reconstruction in the past 6–36 months. Participants completed the Knee Osteoarthritis Outcome Score and the Tegner Activity Score. Descriptive statistics were used to analyze quantitative data. Interviews were recorded, transcribed and analyzed using the general inductive approach to develop key themes. Results: Participants had not returned to pre-injury knee-related activity levels (Tegner score: 7 pre-injury; 4 current). The theme of a disruptive "journey" emerged with two sub-themes of "loss of identity" and "life at the present, " influenced positively and negatively by "support systems" and experience with the "care pathway." This unequivocally negative experience resulted in irrevocable changes to their lives, reflected by current lower knee-related quality of life. Conclusions: Anterior cruciate ligament injury and rehabilitation thereof have a profound influence in the individual's identity. The results imply that a broader approach is needed within the rehabilitation process to address psychosocial factors, in addition to physical impairments and function. Implications for rehabilitation: Anterior cruciate ligament rupture has a profound influence on patients' understanding of their individual identity. Support systems the patients have in place influence the patients' experience of the care pathway. Understanding psychosocial responses and implementing appropriate strategies and interventions for these may be critical for rehabilitation of these patients.